Environmental impact evaluation of crumb rubber industry production process by life cycle assessment (LCA) method (case study: PT FRP). Issue 1 (November 2021) - Yerdianti, A; Aziz, R
Abstract: PT FRP produces crumb rubber SIR 20 with a total annual production of 42.000 tons. This study aims to analyze the environmental impact of 1-ton crumb rubber production using the Life Cycle Assessment (LCA) method to be further explored for recommendations for ecological improvement. LCA was carried by a gate-to-gate scope using SimaPro software with the eco-indicator 99 method. The steps for completing this research refer to ISO 14040:2016. Characterization step results from the category of fossil fuels impact have the highest value (931 MJ surplus). The total value of the single score generated is 369 Pt, with the highest impact value is respiratory inorganics. The dryer drying process, the usage of electricity, and the generator and boiler are four production processes that significantly impact the environment. Improvement recommendations given to reduce the effects of the four processes are using an economizer in the boiler, the combination of fuel used by the boiler, and substitution of diesel fuel with Pertamina Dex as generator's fuel.